2012
DOI: 10.1038/npp.2012.263
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Serum Levels and Genotype: Association with Depression during Interferon-α Treatment

Abstract: Depression has been associated with inflammation, and inflammation may both influence and interact with growth factors such as brainderived neurotrophic factor (BDNF). Both the functional Val66Met BDNF polymorphism (rs6265) and BDNF levels have been associated with depression. It is thus plausible that decreased BDNF could mediate and/or moderate cytokine-induced depression. We therefore prospectively employed the Beck Depression Inventory-II (BDI-II), the Hospital Anxiety and Depression Scale (HADS), and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 125 publications
0
77
1
Order By: Relevance
“…BDNF was also known to be a resilience biomarker for IFN-associated MD in CHC patients [12]. Our study failed to replicate this finding, but we reported for the first time that adiponectin may also be a resilience biomarker for MD in CHC patients.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…BDNF was also known to be a resilience biomarker for IFN-associated MD in CHC patients [12]. Our study failed to replicate this finding, but we reported for the first time that adiponectin may also be a resilience biomarker for MD in CHC patients.…”
Section: Discussioncontrasting
confidence: 69%
“…brain-derived neurotrophic factor (BDNF), tumor necrosis factor (TNF)-α, its soluble variant (sTNFR2), IL-23 and RANTES, associated with neuropsychiatric symptoms (depression, anxiety, fatigue and/or pain) [11]. In patients with CHC, BDNF has been shown to influence resilience to depression during IFN-based therapies [12]. However, variation in either BDNF or other inflammatory mediators investigated to date does not fully explain the substantial heterogeneity associated with the risk of developing IFN-induced depression.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of work performance increases with infection and with IFN treatment. Behavioral responses to cytokines can benefit an organism by promoting conservation of energy and allocation of resources to combat infection or recovery from injury along with behaviors that may elicit care giving from others [40,41].…”
Section: Resultsmentioning
confidence: 99%
“…Pro-inflammatory cytokines negatively regulate hippocampal BDNF expression and signal transduction [44]. There is a bidirectional relationship between BDNF and cytokines with a plausible role for this interaction in the etiology of major depressive disorders [45]. Accordingly, administration of lipopolysaccharide (LPS), a major bacterial TLR-4 ligand, caused cognitive impairment in animal models through increased expression of pro-inflammatory cytokines alongside a reduction in BDNF levels in the hippocampus [40].…”
Section: Discussionmentioning
confidence: 99%